Penerapan Hukuman Mati Dalam Kasus Narkotika di Indonesia - Hardian Estu Prabowo; Ernu Widodo; Vieta Cornelli; Hartoyo . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
The circulation and abuse of narcotics in Indonesia has reached avery alarming stage and has had a far-reaching impact on socialorder, public health, and the future of the nation's future generations.The government has responded to this phenomenon by imposingstrict sanctions, including the death penalty, against perpetrators ofnarcotics crimes as a form of repression and deterrent. This studyaims to examine the legal regulations regarding the death penalty fornarcotics crimes in Indonesia and assess the effectiveness of itsimplementation in eradicating narcotics crimes. The research methodused is normative juridical with a legislative approach and casestudies. The results show that the legal basis for the death penalty innarcotics cases is stipulated in Law Number 35 of 2009 and theCriminal Code, and is reinforced by the decisions of the ConstitutionalCourt. However, its implementation continues to reap pros and consfrom a human rights perspective. The effectiveness of the deathpenalty in eradicating narcotics trafficking is considered suboptimaldue to the high number of violations, weak law enforcement, andpotential procedural violations. Therefore, an evaluation of the deathpenalty policy is necessary to ensure it aligns with the principles ofjustice, human rights protection, and the objectives of criminal lawitself.